Fear of falling reduced by a lay led home-based program in frail community-dwelling older adults: A randomised controlled trial. (January 2017) - Kapan, A.; Luger, E.; Haider, S.; Titze, S.; Schindler, K.; Lackinger, C.; Dorner, T.E.
Highlights: FOF is associated with physical parameters, especially physical performance. Our results for FOF – a reduction of 10% – are consistent with those which were obtained by health professionals. Increasing muscle strength and improving physical performance is associated with a reduction in FOF. A high concern about falling in this population was already shown in the beginning of the study. Abstract: Background: In older adults, fear of falling (FOF) leads to a decline in daily physical activity quality of life and an increased risk of falling. The aim of this randomised controlled trial was to assess the effects of a 12-week home-based intervention program carried out by lay volunteers on FOF in frail older adults. Methods: Thirty-nine participants were randomised to a physical training and nutrition (PTN) group and 41 participants to a social support (SOSU) group. In the PTN group, strength training and conversation about optimising nutrition were performed twice weekly, and the SOSU group received home visits without intervention. FOF and change of FOF were assessed using the Falls Efficacy Scale – International (FES-I). The Short Physical Performance Battery (SPPB), the Physical Activity Scale for the Elderly (PASE) and maximum handgrip strength and their changes were also assessed. Results: The mean FES-I score at baseline was 42.7 points and was significantly associated with the SPPB and PASE scores. The FES-I score significantly changed in the PTN group from 44.1 to 39.9 points over the course of the intervention. Twenty-seven percent of the participants showed a decreased FES-I score of at least 4 points. This decrease was associated with an increase in the SPPB score and an increase in handgrip strength Conclusion: A 12-week structured physical training and nutrition intervention carried out by lay volunteers, which leads to an increase in physical activity and improved physical performance, can reduce FOF by about 10%.